The effect of Innovation Products, Lifestyle and Brand Image on Purchase Decision of Datsun Type Cars - Febria Rida Vitantri; Saptianing - Saptianing; Iwan - Hermawan (JOBS (Jurnal Of Business Studies), 2020)
Innovation is an important element for creating new opportunities in a car industry business. Each year, vehicle manufacturers issue the latest types of vehicle models. The development of the number of cars in Indonesia is not in line with the sales of Datsun cars at Indomobil's Puri Anjasmoro Semarang branch. The purpose of this study is to determine the influence of product innovation, lifestyle, and brand image on Datsun car purchasing decisions either simultaneously or partially. This research is a quantitative study using a questionnaire approach and literature study with a sample size of 71 respondents. The model used is multiple linear regression analysis Y = -1.129 + 0.105 X1 + 0.424 X2 + 0.510 X3. With the results of the F test, the sig value is 0.000 which shows that simultaneously the variable product innovation, lifestyle and brand image have a significant effect on purchasing decisions. The result of the determination coefficient (R2) is 76.3%, which means that the variable product innovation, lifestyle and brand image contributes to the influence of purchasing decisions. Meanwhile, 23.7% was influenced by other variables outside the model. T test results obtained sig value of product innovation (X1) sig = 0.356 lifestyle (X2) sig = 0.002 and brand image (X3) Sig = 0.000. Based on these results, the product innovation variable has no significant effect on purchasing decisions, while thevariables lifestyle and brand imagehave a significant effect on purchase intention. Based on the research of the three variables above, the Brand Image variable is the variable that most influences the Purchasing Decision